Pengaruh Pergantian Auditor, Spesialisasi Auditor, Profitabilitas, dan Leverage terhadap Audit Report Lag - Salsabila Zalfa Azhar; Auliffi Ermian Challen (Juara: Jurnal Riset Akuntansi, 2023)
Every year there is an increase in the number of issues who report financial reports that are not on time. Therefore, the purpose of this research is to investigate the impact of auditor change, auditor specialty, profitability, and leverage on audit report lag. The quantitative research strategy is correlational and relies on secondary data, specifically companies listed on the IDX between 2019 and 2021. A total of 97 companies were chosen using a purposive sampling technique. This study's data were analyzed utilizing the multiple linear regression analysis approach, which was aided by the SPSS version 29 application. The study's findings show that auditor change and leverage have no effect on audit report lag, however auditor speciality and profitability have a negative effect on audit report lag.